Development of a multi-patient ventilator circuit with validation in an ARDS porcine model - Wankum, Benjamin P. (J Anesth, 2021)
PURPOSE: The COVID-19 pandemic threatens our current ICU capabilities nationwide. As the number of COVID-19 positive patients across the nation continues to increase, the need for options to address ventilator shortages is inevitable. Multi-patient ventilation (MPV), in which more than one patient can use a single ventilator base unit, has been proposed as a potential solution to this problem. To our knowledge, this option has been discussed but remains untested in live patients with differing severity of lung pathology. METHODS: The objective of this study was to address ventilator shortages and patient stacking limitations by developing and validating a modified breathing circuit for two patients with differing lung compliances using simple, off-the-shelf components. A multi-patient ventilator circuit (MPVC) was simulated with a mathematical model and validated with four animal studies. Each animal study had two human-sized pigs: one healthy and one with lipopolysaccharide (LPS) induced ARDS. LPS was chosen because it lowers lung compliance similar to COVID-19. In a previous study, a control group of four pigs was given ARDS and placed on a single patient ventilation circuit (SPVC). The oxygenation of the MPVC ARDS animals was then compared to the oxygenation of the SPVC animals. RESULTS: Based on the comparisons, similar oxygenation and morbidity rates were observed between the MPVC ARDS animals and the SPVC animals. CONCLUSION: As healthcare systems worldwide deal with inundated ICUs and hospitals from pandemics, they could potentially benefit from this approach by providing more patients with respiratory care. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00540-021-02948-2.